The Mediating Role of Mental Toughness in the Relationship Between Burnout and Perceived Stress Among Hungarian Coaches - Eszter Bíró; László Balogh (Sports)
This study aimed to explore the relationship between perceived stress, burnout, and mental toughness, and investigate how mental toughness mediates the relationship between perceived stress and burnout among Hungarian coaches. Three hundred and thirty-three active coaches completed anonymous self-report questionnaires assessing burnout (CBQ), mental toughness (SMTQ), and perceived stress (PSS). In the international comparison, Hungarian coaches indicated significantly higher burnout levels than those investigated in previous international research. PLS-SEM results showed that coaches with higher stress levels are less likely to experience burnout. Furthermore, mental toughness serves as a buffer between stress and burnout; however, the buffering effects of its various subfactors on different dimensions of coaching burnout vary. Consequently, further research is necessary to fully understand the mitigating effects of mental toughness, particularly by analyzing coping strategies, motivation, and success. Our research unequivocally indicates that the integration of targeted stress management training into coaching education is crucial for effectively addressing the emotional challenges inherent in the profession. By incorporating workshops that focus on self-awareness and emotion regulation strategies, coaching programs can substantially reduce the risk of burnout and promote the well-being of coaches. These findings underscore the vital importance of embedding practical stress management interventions within coach development initiatives to cultivate more resilient and effective coaching professionals.